(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The tax system of Uzbekistan has its own characteristics, and it can be compared with other Asian countries. Income tax: In Uzbekistan the rate is 7.5%, which is lower than in many other countries. Personal income tax: The rate is 12%, which is also relatively low. Social tax : For budgetary organizations - 25%, for others - 12%. Turnover tax: Rate - 4%.